The western conifer seed bug Leptogloáus Heidemann, 1910 (Heteroptera: Coreidae) in Portugal - Sousa, E.=700 1 Naves, P.
(Es, En)
Ilus; 12 ref.
Keywords: PINUS; LEPTOGLOáUS; PLAGAS DE PLANTAS; CONOS; SEMILLAS; ESPAÑA; CHINCHE DE LOS PIÑONES; BOLETIN DE SANIDAD VEGETAL: PLAGAS